Investigating the Impact of Learning Organization Components on Organizational Innovation (Case Study: Islamic Azad University) - Jafarzadeh Ghadimi, Robab; Enayati, Taraneh; Salehi , Mohammad (Iranian Journal of Educational Sociology, 2022)
Purpose: The purpose of the study is to provide the impact of learning organization components on innovation in the Islamic Azad University. The prediction of the risks and opportunities facing organizations in the future will give us the opportunity to decide, before we get into trouble. Planning for organizational change and improvement through lifelong learning to cope with organizational challenges for sustainable organizational development and survival is a prerequisite. Methodology: This study is descriptive- survey research. The study population were all the faculty members of Islamic Azad University in Shabestar in 2016 (n=271) that 170 members were selected by stratified random on base of Kerjeci and Morgan table. Findings: To collect the data, Goh learning organization questionnaire and Saatchi & et al innovation questionnaire was used. The construct validity of learning organization questionnaire and organizational innovation were confirmed. Learning organization reliability was calculated α = (0.843) and organizational innovation was calculated α = (0.811) using Cronbach's alpha coefficient. Obtained data by SPSS and LISREL software and the calculation of descriptive and inferential statistics (Confirmatory Factor Analysis, structural equations model) were analyzed. Conclusion: The results showed that the components of learning organization had positive and significant impact on organizational innovation and model fitting was confirmed.